PASAR GIWANGAN SEBAGAI OUTDOOR LEARNING MATA PELAJARAN IPS DI MIN YOGYAKARTA II (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
This paper intends to answer the question of interests and abilities of students in studying IPS. By utilizing the Bus Market as an arena for learning outside the classroom is one solution that can be used to answer these problems. Besides being able to improve the social skills of students with surrounding communities, utilization Giwangan Market is another form of innovation learning outside the classroom. In social studies, the real community is a large laboratory which should be empowered.